Features of the legal status of judges: Kazakhstan experience and foreign realities - Yesembayeva, Zhanar (Opción, 2018)
The special value in the constitutional state carries out functioning of the judicial authority which is the guarantor of justice implementation, supremacy of law and rule of law. The main role in the judicial authority mechanism is assigned to the judge as the maker of justice. In this regard, legal status of the judge demonstrates the level of development of judicial authority, quality of justice and its independence. The main requirements, imposed to the candidates for judges in Kazakhstan, are highlighted in article. An author is revealed the current problems. The comparative research of foreign experience is conducted.